2018
DOI: 10.21873/anticanres.12331
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Evidence Supporting the Vitamin D-Cancer Prevention Hypothesis in 2017

Abstract: The vitamin D-cancer prevention hypothesis has been evaluated through several types of studies, including geographical ecological studies related to indices of solar ultraviolet-B (UVB) dose (the primary source of vitamin D for most people), observational studies related to UVB exposure or serum 25-hydroxyvitamin D [25(OH)D] concentrations, laboratory studies of mechanisms, and clinical trials. Each approach has strengths and limitations. Ecological studies indirectly measure vitamin D production and incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 73 publications
1
18
0
Order By: Relevance
“…More than 8000 studies have been performed to investigate the inverse correlation between vitamin D, its metabolites, and cancer [ 43 ]. Women with a higher solar UVB exposure in the Third National Health and Nutrition Examination Survey (NHANES III) showed 50% incidence of breast cancer compared to those with lower solar exposure [ 44 ].…”
Section: Vitamin D and Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…More than 8000 studies have been performed to investigate the inverse correlation between vitamin D, its metabolites, and cancer [ 43 ]. Women with a higher solar UVB exposure in the Third National Health and Nutrition Examination Survey (NHANES III) showed 50% incidence of breast cancer compared to those with lower solar exposure [ 44 ].…”
Section: Vitamin D and Cancermentioning
confidence: 99%
“…Meta-analyses show significant inverse correlations between serum 25(OH)D concentration and incidence of bladder, breast, colorectal, kidney, and lung cancer [ 43 ]. Two studies were reported for colon and rectal cancer.…”
Section: Vitamin D and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, newer and more extensive studies describing the pleiotropic effects of vitamin D and the importance of its deficiency in many diseases, not strictly related to changes occurring in the skeletal system, have been published. These research issues concern cancer diseases [ 3 , 4 , 5 ], cardiovascular disease [ 6 ], diabetes [ 7 ], as well as mental illnesses [ 8 , 9 , 10 ]. The main sources of vitamin D are both oral intake and synthesis in the skin.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D is believed to reduce the risk of chronic illnesses and neoplasms [ 37 , 61 ]. According to the review by Grant, the available scientific evidence supports the notion of vitamin D supplementation as a cancer prevention method [ 81 ].…”
Section: Discussionmentioning
confidence: 99%